(untitled) (International Current Pharmaceutical Journal, 2012)
Arsenic contamination in groundwater is a global health challenge. A large number of people worldwide are affected by arsenic poisoning. Paracetamol is a widely used analgesic-antipyretic drug. Effect of arsenic on paracetamol binding to protein has been investigated using two site specific probes and equilibrium dialysis method was used for the experiment. In absence of any site specific probes free concentration of paracetamol bound to bovine serum albumin increased from 3.95 ± 1.164% to 25.36 ± 1.164%. In presence of site-I specific probe warfarin sodium the % release of drug was steady at around 14%. But in presence of site-II specific probe an increment of free drug concentration was observed from 14.38 ± 1.164% to 54.72 ± 1.552%. Thus it can be assumed that the free concentration of paracetamol was increased to a greater extent in presence of arsenic and probably arsenic bound to site-II of BSA. Thus arsenic may displace paracetamol by binding with high affinity binding site, site-II in the BSA and probably arsenic has little effect to site-I. DOI: http://dx.doi.org/10.3329/icpj.v1i11.12061 International Current Pharmaceutical Journal 2012, 1(11): 361-365